Pendidikan Seks Anak dalam Keluarga di Kecamatan Sagulung Batam - Fatimah Nur Hidayah; Emmy Solina; Marisa Elsera (Social Issues Quarterly, 2023)
This study aims to find out how the role of the family in children's sex education in Sagulung, Batam city. research using qualitative research methods with a descriptive approach. Data collection techniques in this study used semi-structured interviews, observation, and documentation. The sampling technique in this study used purposive sampling with 8 informants who were divided according to the criteria, namely 4 informants as parents who rejected the idea that sex education for children was taboo. 1 informant as a parent who lacks awareness and their child's need for sex education, 7 informants as a parent who agree with child sex education. Based on the findings of researchers, some parents still consider sex education to be taboo and the sex education that is implemented in families in Sagulung District uses basic understanding to children, by providing understanding and differences in female and male genitalia. In this finding, the researchers found that parents were hampered by providing sex education to their children, that parents felt ashamed or taboo about expressing and discussing sex issues with their children.